Implementasi Dashboard Untuk Visualisasi Data Penerimaan Mahasiswa Baru Studi Kasus : Universitas Kristen Duta Wacana - Vanesha Glorya Priskilla; Yetli Oslan; Lussy Ernawati (Jurnal Terapan Teknologi Informasi, 2021)
New Student Admissions activities at an University needs to be monitored to determine the performance of Admission and Promotion. Admission data can be processed and analyzed to determine the expo destination schools, promotion locations, and appropriate potential areas. In addition, the results of Admission data processing can be used to determine the fluctuation of enthusiasts in the Majors from previous periods or the comparison of the number of enthusiasts between Majors. For that reason we need a dashboard as a tool to help user for analyze, monitor and be taken into consideration in making strategic decisions related to Admission activities. The implemented dashboard consists of a collection of information that is visualized in graphs and numbers. The users of the dashboard are employees of the Admissions and Promotion Unit, Head of Majors for each department, and Administrators.                   There are 6 dimensions displayed in the dashboard, namely time, region, test route, path transfer, prospective students, and school origin. The data of new student admissions is processed and stored into the data warehouse through the ETL process. Furthermore, the data warehouse is used as data storage for the implementation of a web-based dashboard application using the PHP programming language. The implemented dashboard consists of Admission information that is visualized into charts and numbers. the graphs that used in PMB data visualization include bar charts, doughnut charts, pie charts, column charts, line charts, and map charts.